Case report: Detection of fetal trisomy 9 mosaicism by multiple genetic testing methods: Report of two cases - Ma, Na; Zhu, Zhenhua; Hu, Jiancheng; Pang, Jialun; Yang, Shuting; Liu, Jing; Chen, Jing; Tang, Wanglan; Kuang, Haiyan; Hu, Rong; Li, Zhuo; Wang, Hua; et al. (Frontiers in Genetics, 2023)
Chromosomal mosaicism remains a perpetual diagnostic and clinical dilemma. In the present study, we detected two prenatal trisomy 9 mosaic syndrome cases by using multiple genetic testing methods. The non-invasive prenatal testing (NIPT) results suggested trisomy 9 in two fetuses. Karyotype analysis of amniocytes showed a high level (42%–50%) of mosaicism, and chromosomal microarray analysis (CMA) of uncultured amniocytes showed no copy number variation (CNV) except for large fragment loss of heterozygosity. Ultrasound findings were unmarkable except for small for gestational age. In Case 1, further umbilical blood puncture confirmed 22.4% and 34% trisomy 9 mosaicism by CMA and fluorescent in situ hybridization (FISH) respectively. After comprehensive consideration of the genetic and ultrasound results, the two gravidas decided to receive elective termination and molecular investigations of multiple tissue samples from the aborted fetus and the placenta. The results confirmed the presence of true fetoplacental mosaicism with levels of trisomy 9 mosaicism from 76% to normal in various tissues. These two cases highlight the necessity of genetic counseling for gravidas whose NIPT results highly suggest the risk of chromosome 9 to ascertain the occurrence of mosaicism. In addition, the comprehensive use of multiple genetic techniques and biological samples is recommended for prenatal diagnosis to avoid false-negative results. It should also be noted that ultrasound results of organs with true trisomy 9 mosaicism can be free of structural abnormalities during pregnancy.